What are they tweeting about? The online claim making structure of the 2021 colombian protests (2021)
Aims: Using the case of the 2021 Colombian National Stoppage, we show that a key role of Social Networking Services (in this case, Twitter) is to provide a parallel, and relatively autonomous, venue for claim making interactions. Methodology/Approach: We extract terms and mentions from an original corpus of tweets related to the 2021 Colombian National Stoppage, in order to create a series of networks of cooccurrence. Findings: We find that there were three central conversations (over grievances, contentious events, and calls for help); that mentioned actors were intuitively grouped together according to traditional party oppositions; but that they were embedded in particular conversations depending on their position in a simpler prestige hierarchy. Value: While the impact of SNS platforms on mobilization has been mostly studied from a technological and organizational perspective, we propose to center our discussion on what we take to be the crux of contentious politics, namely, claim making interactions.